Collective bargaining and telework: new acting challenges - Sierra-Hernaiz, Elisa (Acciones e Investigaciones Sociales, 2023)
Collective bargaining plays a fundamental role in regulating and adapting key issues of teleworking, such as the prevention of occupational risks specifically adapted to this type of services; digital disconnection rights; the rights to work-family balance with a gender perspective or virtual harassment or cyberbullying. However, until now, it has focused mainly on regulating formal aspects or material content without taking into account in the majority of collective agreements the peculiarities that teleworking presents in these four questions, which may mean creating new inequalities or give rise to new occupational risks
Keywords: teleworking; collective bargaining; challenges